Theory and empirical evidence of the gender wage gap - Ali, Hassan; Othman, Noraini; Zakaria, Nazlina (2005)
Women participation in the labor force has steadily increased over the last several decades, Despite this, women still remain in lower status, less interesting and less well paid jobs. Differences in family and economic roles between men and women have resulted in wage discrimination between men and women. Attempts to explain the gender wage differential generally rely on human capital and labor market segmentation theories. The human capital theory attributes wage differentials to differences in education, training and work experience. Labor market segmentation theory on the other hand attribute wage differentials to the segmentation of the labor market into primary and secondary sectors. The human capital theory remains the dominant theory explaining wage differentials between male and females. Research evidence does suggest that differences in the level of education and experience between male and female influence wages.